1999
DOI: 10.1038/sj.bjc.6690086
|View full text |Cite
|
Sign up to set email alerts
|

Is early post-operative treatment with 5-fluorouracil possible without affecting anastomotic strength in the intestine?

Abstract: Early post-operative local or systemic administration of 5-fluorouracil (5-FU) is under investigation as a means to improve outcome after resection of intestinal malignancies. It is therefore quite important to delineate accurately its potentially negative effects on anastomotic repair. Five groups ( n = 24) of rats underwent resection and anastomosis of both ileum and colon: a control group and four experimental groups receiving daily 5-FU, starting immediately after operation or after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
0
19
0
3
Order By: Relevance
“…As many series (19), important part of our morbidity is represented by leakages. It has been proved that the use of heated chemotherapy has a detrimental effect on the strength of colonic anastomosis, especially during the early postoperative period (until day 10) (20,21). This may cause anastomotic failure and postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…As many series (19), important part of our morbidity is represented by leakages. It has been proved that the use of heated chemotherapy has a detrimental effect on the strength of colonic anastomosis, especially during the early postoperative period (until day 10) (20,21). This may cause anastomotic failure and postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hydroxyproline levels are important parameters in the tissue repair process [34,35] . Some studies have found that 5-FU decreases the hydroxyproline content of wounds [19,21] . There were significant differences in hydroxyproline levels at the anastomotic segments on both the 3rd and 7th PO days in the IV group compared to the IP group.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction, 5-FU has remained the cornerstone of adjuvant treatment for colorectal cancer. A number of clinical and experimental data are available on the effects of 5-FU, either alone or in combination with other chemotherapeutic agents, on wound healing [19][20][21][22] . In the adjuvant therapy of colorectal cancers, 5-FU was used alone in prolonged systemic regimens or in combination with other agents [22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Giving early postoperative 5‐FU has been investigated to improve outcomes after resecting intestinal malignancies 27. Surgeons have been reluctant to prescribe 5‐FU in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%